The Road Less Traveled: Ciliary Sulcus Implantation of the Preserflo MicroShunt - Meishar Meisel; Eran Berkowitz; Avi Schwalb; Beatrice Tiosano (Case Reports in Ophthalmology)
Introduction: Herein, we report on the option and clinical advantage of the Preserflo MicroShunt insertion into the posterior chamber ciliary sulcus in a patient with advanced pseudoexfoliation glaucoma at a high risk of corneal decompensation. Case Presentation: We describe a 64-year-old advanced pseudoexfoliation glaucoma patient who despite maximal tolerated medical therapy and two failed glaucoma surgeries, still suffered from uncontrolled intraocular pressure (IOP) of 36 mm Hg in his left eye. The patient underwent the implantation of the Preserflo MicroShunt. The shunt was placed nasally into an area of unscarred conjunctiva, with the anterior part of the shunt inserted into the ciliary sulcus. Postoperatively, the patient’s IOP dropped to 6 mm Hg on the first day and stabilized at 11 mm Hg at the 6-month mark. An elevated, posteriorly located bleb was observed, and the patient no longer required additional topical medications. Endothelial cell (EC) count remained stable with no signs of corneal edema. The patient did not experience any serious postoperative complications. Conclusion: Implantation of the Preserflo MicroShunt into the ciliary sulcus appears to be a viable option for patients at high risk of corneal decompensation, hence, offering effective IOP control while minimizing EC loss. Further studies with larger patient groups are warranted to better evaluate the safety and efficacy of this technique.